Développement d’instruments d’évaluation Higher Order Thinking Skills (HOTS) en utilisant de l’application Plickers - Desy Wulandari; Hesti Fibriasari (Universitas Negeri Semarang, 2024)
This research aims to develop French assessment instruments based on higher-order thinking Skills (HOTS) using the Plickers application to improve student learning outcomes and critical thinking skills. This research used Fenrich’s development model, which comprises six stages, namely (1) analysis, (2) planning, (3) design, (4) development, (5) implementation, and (6) evaluation and revision. However, in its implementation, only three stages were carried out, namely the analysis stage, the design stage, and the development stage. The analysis stage consists of analyzing student needs, analyzing the curriculum, and analyzing the materials. At the design stage, an assessment instrument was designed based on a curriculum composed of greetings, introducing oneself, daily life, the weather, congratulating someone, and situating oneself in the escape and the family. At the development stage, an assessment instrument based on HOTS was developed. In the development process, there are two main obstacles: determining the appropriate operational verbs for the material and determining the contextual questions, personalized stimulus items, and response selection. The draft assessment instrument has been validated by materials and media experts. The results of the materials validator test were 87.5%. The results of the media validator test were 89.2% in the correct category. Based on this research, we can see that the HOTS material and the Plicker application are suitable for use in learning French at school.